Bridging frailty and burns: defining acute burn injury as a cause of long-term frailty - Panayi, Adriana C.; Herndon, David N.; Branski, Ludwik; Sjöberg, Folke; Hundeshagen, Gabriel (Maturitas, 2024)
Although our understanding of frailty has evolved and multiple indices have been developed, the impact of burn injuries on long-term health has been overlooked. With over 11 million annual cases globally, burns affect all demographics, although socioeconomic disparities are evident. With survival rates improved, morbidity among survivors is becoming more evident, and shows similarity to predictors of frailty. Some of the chronic effects of burns, including mental health issues and increased risks of disease, mirror frailty markers. Studies show burn survivors have lower life expectancy, independent of burn severity. Integrating burn history into frailty assessments and establishing specialized long-term care can mitigate this frailty risk. Improved interdisciplinary follow-up and research are vital for enhancing burn survivors' quality of life and longevity.